PEMANFAATAN DAUN PEGAGAN SEBAGAI BAHAN PEMBUATAN SABUN ALAMI “SABUN ALAMI DAUN PEGAGAN UNTUK PENINGKATAN DAYA TAHAN TUBUH” - murtiyani; Fikriyatul Qoriah; Sri Jumini (CATHA SAINTIFICA, 2026)
This research aims to analyze the effect of variations in the concentration of gotu kola leaf extract (Centellaasiatica) on the physical, chemical and functional characteristics of natural solid soap.  This research used experimental methods by designing four solid soap formulations: control (without gotu kola leaf extract), formulation A (with 5% extract), formulation B (with 10% extract), and formulation C (with 15% extract). Parameters tested include pH, water content, hardness, foam stability and antioxidant activity. The results showed that increasing the concentration of gotu kola leaf extract significantly affected the characteristics of the soap. The formulation with the highest extract concentration (15%) shows a pH value that remains within the safe range for the skin (8.5-9.0) and a stable water content, which is important for product shelf life. In addition, this formulation also showed increased hardness and better foam stability compared to the control. Adding gotu kola leaf extract at a concentration of 15% produces a natural solid soap that provides the benefits of increasing body endurance, increasing cell regeneration, reducing signs of aging and maintaining skin without negative effects.